Pediatric Rehabilitation Services for Children With Cerebral Palsy: What Can Existing Data Sources Tell Us?. Issue 2 (April 2017) - Gannotti, Mary E.; Bailes, Amy; Bjornson, Kristie; O'Neil, Maggie; Grant-Buettler, Marybeth; Dusing, Stacey
Abstract : Knowledge about associated service utilization patterns and positive outcomes in children with cerebral palsy (CP) of varying levels of severity is a national priority. Families, clinicians, program directors, and policy makers need this information for clinical decision-making and service planning. Existing data sources in the United States that contain information about children with CP, their health, function, well being, and utilization of health services may add to our existing knowledge. We provide a summary of fourteen national, state, and local sources' data: where the data come from, challenges and/or specific considerations when using or accessing information, and specific data elements included. Currently available sources of data can provide meaningful information for policy, practice, and program development. We propose questions for future inquiry and suggest elements that may be useful for when developing data sources specific to physical therapy and individuals with CP. A physical therapy specific registry is warranted. Abstract : Supplemental Digital Content is Available in the Text.This is a summary of fourteen national, state, and local sources of data in the United States that provide information about children with cerebral palsy, their health, function, well being, and utilization of health services. Despite limitations, currently available sources of data may provide meaningful information for policy, practice, and program development.